Learning in the Virtual Environment: Instructors’ Strategies in Enhancing Interaction in ESL Online Classes - Ariffin, Kamisah; Darus, Norizul Azida; Abdul Halim, Norhajawati (LEARN Journal: Language Education and Acquisition Research Network, 2022)
The common features attributed to face-to-face classroom are rather difficult to emulate in a virtual learning environment. This is because participants may not feel obligated to participate when they do not see each other physically. This study examined the instructors’ strategies in fostering interaction in their online classes. Using the Classroom Assessment Scoring System (CLASS) as a framework for investigation, the study observed recorded ESL classes under the three domains of interactions between instructors and learners, that is, emotional support, classroom organization and instructional support. This is a qualitative study and therefore, for the purpose of data collection, 6 English Language classes which were carried out virtually from a public university were recorded during lectures for 6 weeks to observe both instructors and learners. The findings indicate that all the three domains of interactions were related and essential since virtual classrooms were still new not only to students, but also the instructors. The findings also found evidence that classrooms categorized by a positive emotional climate with sensitivity to the needs of the learners, usage of engaging instructional learning formats and at the same time emphasized on higher order thinking skills were all associated to learners’ achievement. It is hoped that the findings can contribute to the pedagogical techniques for enhancing interactions in online learning environment.